1989
DOI: 10.1182/blood.v73.2.588.588
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of guanine nucleotide binding proteins in neutrophil activation and priming by GM-CSF

Abstract: Pre-incubation of human neutrophils with pertussis toxin significantly inhibited the neutrophil-directed biologic actions of granulocyte- macrophage colony-stimulating factor (GM-CSF) in three separate assays: the induction of c-fos mRNA, the enhancement of both platelet- activating factor-induced mobilization of intracellular calcium, and stimulation of leukotriene synthesis by the calcium ionophore A23187. Cholera toxin did not have an effect on the latter two assays. Pre- treatment of human neutrophils with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…We showed that PT did not inhibit the priming of PLA 2 by GM-CSF, indicating that a PT-sensitive heterotrimeric G-protein, such as Gi, was not involved. Our data are in accord with those of DiPersio et al (1988), who found no effect of PT on GM-CSF-mediated priming of leukotriene production, but contrast with other studies (Gomez-Cambronero et al, 1989;Corey & Rossoff, 1989;McColl et al, 1989), showing that other effects of GM-CSF were inhibited by PT. Whilst the PLA 2 activity of unprimed cells was not inhibited by genestein, in confirmation of previous work (Atluru et al, 1992), it specifically blocked the GM-CSF primed response, suggesting the involvement of a tyrosine kinase in the GM-CSF-mediated Phospholipase A 2 and Neutrophil Priming # 1996 Blackwell Science Ltd, British Journal of Haematology 92: 804-814 priming of PLA 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that PT did not inhibit the priming of PLA 2 by GM-CSF, indicating that a PT-sensitive heterotrimeric G-protein, such as Gi, was not involved. Our data are in accord with those of DiPersio et al (1988), who found no effect of PT on GM-CSF-mediated priming of leukotriene production, but contrast with other studies (Gomez-Cambronero et al, 1989;Corey & Rossoff, 1989;McColl et al, 1989), showing that other effects of GM-CSF were inhibited by PT. Whilst the PLA 2 activity of unprimed cells was not inhibited by genestein, in confirmation of previous work (Atluru et al, 1992), it specifically blocked the GM-CSF primed response, suggesting the involvement of a tyrosine kinase in the GM-CSF-mediated Phospholipase A 2 and Neutrophil Priming # 1996 Blackwell Science Ltd, British Journal of Haematology 92: 804-814 priming of PLA 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Role of a Bordatella pertussis toxin sensitive G-protein. It was previously reported that effects of GM-CSF in several systems is regulated by a Bordatella pertussis toxin sensitive GTPbinding protein (G protein) (Gomez-Cambronero et al, 1989;Corey & Rossoff, 1989;McColl et al, 1989) although other workers found no such effect (DiPersio et al, 1988). To investigate whether pertussis toxin (PT) inhibited GM-CSFmediated priming of PLA 2 , neutrophils were preincubated with concentrations of PT that ranged from 0 to 1 g/ml for 90 min before addition of GM-CSF or diluent followed by stimulation with calcium ionophore (A23187) and measurement of AA release.…”
Section: Mechanism Of Gm-csf Mediated Priming Of Plamentioning
confidence: 99%
“…Several features of this response suggest that, unlike many reported effects of GM-CSF on signalling reactions (e.g. Corey and Rossoff, 1989;McColl et al, 1989) in Ptdlns(3,4,5)P3 (lower panels) or Ptdlns(4,5)P2 (upper panels), the ranges of the individual data points are indicated by error bars. The data for neutrophils incubated with or without staurosporine were reproduced in one further experiment for GM-CSF and three further experiments for FMLP.…”
Section: Discussionmentioning
confidence: 86%
“…In PMN performing 'frustrated' phagocytosis we did not find significant differences in the NF-κB pathway, however, FOS and JUN (the proteins c-fos and c-jun form the transcriptional regulator AP-1) were both increasingly expressed. PMN have been reported to constitutively express family members of FOS and JUN on transcriptional as well as c-fos and c-jun on translational level [32][33][34][35] with the steady state level of their RNA transcripts being rapidly up-regulated in response to several stimuli [36,37]. However, neither the proteins c-jun and c-fos nor the protein AP-1 has been shown to be up-regulated in PMN after exposure to diverse stimuli as indicated by our results and as reported by others [34,35].…”
Section: Discussionmentioning
confidence: 99%